Controls of the global overturning circulation of the ocean - Fabien Roquet; Michael J. Bell; Agatha M. de Boer; David Ferreira; C. Spencer Jones; Joseph H. LaCasce; Casimir de Lavergne; David P. Marshall; David R. Munday; Jonas Nycander; Malin Ödalen (npj Climate and Atmospheric Science)
Abstract The global overturning circulation (GOC) is the largest scale component of the ocean circulation, associated with a global redistribution of key tracers such as heat and carbon. The GOC generates decadal to millennial climate variability, and will determine much of the long-term response to anthropogenic climate perturbations. This review aims at providing an overview of the main controls of the GOC. By controls, we mean processes affecting the overturning structure and variability. We distinguish three main controls: mechanical mixing, convection, and wind pumping. Geography provides an additional control on geological timescales. An important emphasis of this review is to present how the different controls interact with each other to produce an overturning flow, making this review relevant to the study of past, present and future climates as well as to exoplanets’ oceans.